2009
DOI: 10.1007/s10886-009-9670-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Attraction and Quorum Sensing Inhibition in Caenorhabditis elegans Exudates

Abstract: Caenorhabditis elegans, a bacterivorous nematode, lives in complex rotting fruit, soil, and compost environments, and chemical interactions are required for mating, monitoring population density, recognition of food, avoidance of pathogenic microbes, and other essential ecological functions. Despite being one of the best-studied model organisms in biology, relatively little is known about the signals that C. elegans uses to chemically interact with its environment or as defense. C. elegans exudates were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 81 publications
2
36
0
Order By: Relevance
“…Males and females were both attracted to the flow-through and 50% methanol (MeOH) fractions, but they did not respond to the 90% fraction. Based on previous studies with C. elegans, the flow-through fraction contains many common metabolites, such as amino acids and sugars (18,19); some of these metabolites are attractive to nematodes (20), whereas the 50% MeOH fraction is enriched in ascarosides (3,5,21). We, therefore, focused our attention on the 50% MeOH fraction, which was further fractionated using ion exchange solid-phase extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Males and females were both attracted to the flow-through and 50% methanol (MeOH) fractions, but they did not respond to the 90% fraction. Based on previous studies with C. elegans, the flow-through fraction contains many common metabolites, such as amino acids and sugars (18,19); some of these metabolites are attractive to nematodes (20), whereas the 50% MeOH fraction is enriched in ascarosides (3,5,21). We, therefore, focused our attention on the 50% MeOH fraction, which was further fractionated using ion exchange solid-phase extraction.…”
Section: Resultsmentioning
confidence: 99%
“…The nematodes secrete cytokinins that play a role in cell cycle activation and in establishing the feeding site as a nutrient sink in the host roots. Another recent study demonstrated that how nematode secretions (non-proteinaceous compounds) interact with soil-inhabiting bacteria [46 ] by using the model nematode Caenorhabditis elegans. This study will open a new avenue of research to study the chemical interactions of other parasitic nematodes with their hosts.…”
Section: Molecular Communication Between Host and Pathogensmentioning
confidence: 99%
“…The ability of roots to communicate with roots of neighboring plants and other organisms in the rhizosphere has been the focus of increasing attention (1,2). Root secretions of secondary metabolites and volatile organic compounds have been shown to play offensive, defensive, and symbiotic roles (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%